2021
DOI: 10.1186/s43088-021-00100-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and comparison of ℽ-aminobutyric acid (GABA) production by LAB in soymilk using RSM and ANN models

Abstract: Background ℽ-Aminobutyric acid (GABA) is a non-proteinaceous amino acid. In the mammalian nervous system, GABA functions as an inhibitory neurotransmitter. The present study focused on screening and optimization of ℽ-aminobutyric acid (GABA) yield by lactic acid bacteria by using soymilk as basal media. Lactobacillus fermentum (Lb. fermentum) was isolated from sourdough. The qualitative confirmation of GABA production by Lb. fermentum was observed by detecting colored spots on thin layer chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Therefore, RSM with the CCD model was assessed for optimizing GABA production in an L. fermentum isolate. Three variables were analyzed, i.e., glucose concentration, MSG concentration, and incubation time [38]. GABA production by Lactobacillus sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, RSM with the CCD model was assessed for optimizing GABA production in an L. fermentum isolate. Three variables were analyzed, i.e., glucose concentration, MSG concentration, and incubation time [38]. GABA production by Lactobacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Three variables were analyzed, i.e. , glucose concentration, MSG concentration, and incubation time [ 38 ]. GABA production by Lactobacillus sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a higher inoculum (8 log CFU/ mL) increased the microbial cell growth to 9.2 log CFU/mL but yielded 101 mg/L of GABA. Rayavarapu et al 28 showed that the highest amount of GABA produced by L. fermentum was 3.79 g/L and the microbial cell growth was 5.8 log CFU/mL using a 1% of inoculum. However, an increase of inoculum to 2% did not significantly change the GABA production yielding 3.71 g/L and a microbial cell growth of 6.4 log CUF/mL.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, several studies have reported that GABA production by L. plantarum strains could increase at the end of the exponential phase or near the stationary phase (Park et al 2021b). Likewise, Rayavarapu, Tallapragada, and Ms (2021) observed that during the first 24 h of incubation, LABs focused on cell multiplication, and the GABA yield was low but after 48 h the microorganisms reached the stationary phase and the amount of GABA produced was higher.…”
Section: Fermentation Timementioning
confidence: 94%